Il Rigestum comunis Albe: la struttura di un liber iurium dal progetto originario alla fisionomia attuale - Merati, Patrizia (Scrineum, 2013)
The Rigestum comunis Albe is one of the earliest libri iurium in Piemonte and it has been used for a lot of papers about history and diplomatics; nevertheless, after the publication of the critical edition (1903) the codex was lost. Its founding, in 2003, allowed to analyse the book’s structure, to reconstruct its original appearance, to trace the events of its life, so that the liber is not only the case of the sources for the history of the town, but also the protagonist of its own history. The first part (1215) is a faithful reproduction of the whole content of civic archive; after that, periodical updates have been added. Moreover, the scribes used to record on its pages also different kinds of documents, such as banishment lists or statutes’ articles. The form and content analysis of the unities composing the liber let us understand that, in comparison to the orginal project, both their sequence and their number have changed. The use of keeping fascicles unbound, so to make them easier to use in communal offices, was often the cause of their misplacing: because of that, they have been bound in the wrong order and material that was not part of the book has been included. It is likely that there have been some losses, but they are impossible to quantify. So we see a picture of the Rigestum which is different from today’s, but the constant element is the book’s identity: although in changed conditions, it succeedes in meeting the communal records’ conservation needs that led to its drafting.